2016
DOI: 10.21037/jtd.2016.07.58
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of mitral valve prolapse: insights from the Framingham Heart Study

Abstract: The Framingham Heart Study group has described the non-diagnostic variants may evolve into mitral valve prolapse over time. These non-diagnostic variants include minimal systolic displacement, and abnormal anterior coaptation which is measured on surface echocardiography. Computed tomography and cardiac magnetic resonance imaging are evolving and can assess the degree of mitral regurgitation (MR); imaging techniques aside, genetic and proteomic detection of mitral prolapse is also evolving. However, the geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…Mitral valve (MV) surgery is the recommended intervention in patients who have severe mitral regurgitation (MR) or mitral stenosis with signs and/or symptoms despite optimal therapy [1][2][3]. The Framingham study showed an estimated 2-3% prevalence of MV prolapse, a proportion of which will progress to severe MR requiring surgical intervention [4]. Keeping in mind this high burden of disease, it is imperative that the future cardiac surgeons are adequately trained in MV surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Mitral valve (MV) surgery is the recommended intervention in patients who have severe mitral regurgitation (MR) or mitral stenosis with signs and/or symptoms despite optimal therapy [1][2][3]. The Framingham study showed an estimated 2-3% prevalence of MV prolapse, a proportion of which will progress to severe MR requiring surgical intervention [4]. Keeping in mind this high burden of disease, it is imperative that the future cardiac surgeons are adequately trained in MV surgery.…”
Section: Introductionmentioning
confidence: 99%
“…МН изучают давно, и достаточно длительный промежуток времени шли дискуссии по поводу этиологии, особенностей клинического течения, диагностики, лечебной тактики в отношении данного заболевания [1,6,16]. По результатам Фремингемского исследования, МН является самой частой клапанной патологией: умеренная и тяжелая степень в общей популяции встречаются в 1,7% случаев и составляют 60% изолированной хирургии МК [15,19], заболеваемость увеличивается с возрастом -у пациентов старше 75 лет аналогичная степень недостаточности имеет место в 9,3% случаев. Различий по частоте встречаемости в зависимости от пола и этнической принадлежности не обнаружено [23].…”
Section: эпидемиология и этиологияunclassified
“…[9][10][11] In degenerative MV disease, MV prolapse (MVP), which is defined as leaflet protrusion by more than 2 mm above the mitral annular plane, is most often caused by myxomatous degeneration of the MV. 12 Most cases of myxomatous MVP are sporadic, though familial cases have been reported, and MVP is known to occur in association with connective tissue disorders like Marfan and Ehlers-Danlos syndrome. 13 Myxomatous valves demonstrate thickened and redundant leaflets, annular dilation, and elongation of the chordae tendineae, which may rupture over time.…”
Section: Primary Mitral Regurgitationmentioning
confidence: 99%